Reframing Fatherlessness in the Digital Public Sphere: A Maqāṣid-Based Reconstruction through Qawā‘id Fiqhīyah - M. Sa’ad Alfanny; Ach Badri Amin; Ahmad Sholakhuddin Al Af Ghoni (Journal of Digital Sharia and Contemporary Legal Thought, 2026)
The phenomenon of fatherlessness has shifted from the domestic sphere to the digital public space, where social media serves as a medium for articulating personal experiences and fostering collective solidarity. This article analyzes this phenomenon through the lens of Qawā‘id Fiqhīyah to offer a normative framework that transcends the dominance of conventional psychological and sociological approaches. This study argues that the absence of the father’s role can be understood as a non-material social harm (ḍarar) that has an impact on the protection of the soul (ḥifẓ al-nafs) and reason (ḥifẓ al-‘aql). The results of the analysis show that applying the principles of al-ḍarar yuzāl and dar’ al-mafāsid muqaddam ‘alā jalb al-maṣāliḥ confirms the urgency of mitigating and providing psychosocial support, including through digital platforms, as part of efforts to reduce harm. At the same time, the principle of al-‘ādah al-muḥakkamah provides legitimacy for the practice of digital solidarity as a form of contemporary social adaptation. However, this legitimacy remains limited by the principle of non-maleficence (lā ḍarar wa lā ḍirār) to prevent the commodification of trauma and the reproduction of new harm. This article concludes that Qawā‘id Fiqhīyah provides a contextual and comprehensive ethical framework for responding to family crises amid an ever-evolving digital ecosystem.